2023
DOI: 10.4111/icu.20220318
|View full text |Cite
|
Sign up to set email alerts
|

Trends of genital wart in Korea according to treatment method classification: Big data analysis of health care in 2010–2019

Abstract: Purpose The purpose of this study is to investigate disease trend of genital wart through changes in each treatment method over the past 10 years in Korea. Materials and Methods From 2010 to 2019, surgical treatment including cauterization, excision, cryotherapy, and laser therapy, non-surgical treatment such as podophyllin, and surgical treatment for anorectal lesion were extracted and analyzed from 2010 to 2019. For each treatment method, characteristics such as sex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Although most respondents knew that HPV causes genital warts, only about 20% knew genital warts could not be cured, suggesting a potential misconception of genital warts among the respondents. Indeed, there is no cure for genital warts despite available treatments for managing the spread of genital warts and curtailing their spread (Kim et al, 2023). This misconception might affect pharmacy students' ability to make informed decisions on their sexual health and provide proper counselling to patients they encounter in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although most respondents knew that HPV causes genital warts, only about 20% knew genital warts could not be cured, suggesting a potential misconception of genital warts among the respondents. Indeed, there is no cure for genital warts despite available treatments for managing the spread of genital warts and curtailing their spread (Kim et al, 2023). This misconception might affect pharmacy students' ability to make informed decisions on their sexual health and provide proper counselling to patients they encounter in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Điều này có thể giải thích do chúng tôi lựa chọn đối tượng có thương tổn kích thước lớn nên cần thời gian điều trị lâu hơn, nhiều lần hơn nên dễ gây tác dụng phụ và biến chứng hơn. Thời gian điều trị càng lâu thì thương tổn càng lan rộng gây nên vòng xoắn thời gian-kích thước điều đó giải thích tại sau kết quả tốt sau 03 tháng thấp hơn kết quả tốt sau 01 tháng điều trị [6]. Ngoài ra, một số bệnh nhân có tái phát sau 01 tháng điều trị, cũng như một số bệnh nhận có tác dụng phụ như chảy máu, đau, phù nề sau khi phẫu thuật thương tổn có kích thước lớn làm giảm tit lệ kết quả tốt sau 03 tháng điều trị.…”
Section: Bàn Luậnunclassified
“…Recently, the incidence of genital warts has been increasing. Kim et al [3] reported the status of genital warts from 2010 to 2019. In 2010, 15,032 men and 10,176 women were treated, but an increase of 229% and 56% to 49,283 men and 15,920 women, respectively, occurred in 2019.…”
mentioning
confidence: 99%